The Tower - Kapustin, Petr (project baikal, 2020)
The essay is devoted to the tower phenomenon. It is one of the most popular, but also the most mysterious types of buildings and structures. Towers are well-known throughout all nations and all epochs… But are they really known? Maybe towers just permit us to use them? What do we owe to them and why do we love them so much? These and other questions are discussed in the essay.